Hybrid Model of Cash Waqf and Qard hasan for Education Financing: A Sharia Economic Law Perspective - Adi Susandi; Nadya Zahra Virliana (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This qualitative case study examines the hybrid model of cash waqf and qard hasan implemented by BMT ITQAN Bandung for education financing from the perspective of Sharia economic law. Data was collected through in-depth interviews, document analysis, and observation to explore the model's legal architecture, operational mechanisms, and perceived impacts. The analysis suggests that the model presents a legally viable structure, supported by the Indonesian Waqf Law, relevant DSN-MUI fatwas, and the Compilation of Sharia Economic Law (KHES), though it navigates complexities in regulatory harmonization and the permissibility of a revolving waqf fund. Preliminary findings indicate that the integration creates a sustainable, interest-free financing mechanism that appears to enhance access to education for low-income communities while preserving the principal waqf capital. The study also identifies potential socio-economic benefits, including increased educational attainment and strengthened financial inclusion, alongside significant challenges related to fund sustainability, public awareness, and the dual role of BMTs as commercial nazhir. This research contributes to the academic discourse on Islamic social finance by providing a critical, evidence-based case study on the contractual and governance intricacies of integrating waqf with microfinance. It offers practical insights for Islamic microfinance institutions seeking to replicate such models and highlights areas for future research, including longitudinal impact studies and comparative policy analysis.